Lasting recombination and cosmic background radiation spectrum - Aldrovandi, R.; D'Olival, J. B.S. (Springer Nature, 1976)
The thermal decoupling during recombination and the endurance of this process can significantly deform the black-body background radiation spectrum even in the absence of heating sources. Observational data contradicts a flat standard universe but agrees with a low-density model and with a flat matter-antimatter symmetric universe. Evidence is presented against the presumption that matter-antimatter annibilation should necessarily produce large distortions. © 1976 D. Reidel Publishing Company.